Individuals’ compassion and organizational inclusiveness: Case studies of Japanese BCtA companies fighting for global health - KYOKO TOKUDA (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: This paper looks at the employees of hybrid organizations from the perspective of the theory that people’s actions have a profound impact on the nature of those organizations and institutions. It demonstrates how these workers are essential for assisting the world’s poorest people in developing nations. Choosing which subset of the population to market to can be complicated by factors at the level of the organization, such as the nature of the business’s structure, strategies, and products.Method: The sample was selected from among the BCtA member companies in Japan that are engaged in inclusive business in the area of global health. Three companies’ employees were surveyed using a Qualtrics online survey. In addition, respondents were asked to rate their level of risk aversion on a scale from